2016
DOI: 10.1111/jdi.12533
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictive factors in diabetic kidney disease progression

Abstract: Diabetic kidney disease (DKD) represents a major component of the health burden associated with type 1 and type 2 diabetes. Recent advances have produced an explosion of ‘novel’ assay‐based risk markers for DKD, though clinical use remains restricted. Although many patients with progressive DKD follow a classical albuminuria‐based pathway, non‐albuminuric DKD progression is now well recognized. In general, the following clinical and biochemical characteristics have been associated with progressive DKD in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 159 publications
(258 reference statements)
12
119
0
13
Order By: Relevance
“…the longer the duration of diabetes, the more the progression of DN. Similar results were documented (Viswanathan et al 2012; Radcliffe et al 2017). In addition, diagnosed complications, including retinopathy, CVD and neuropathy were significantly more frequent in patients with DN than in patients without DN.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…the longer the duration of diabetes, the more the progression of DN. Similar results were documented (Viswanathan et al 2012; Radcliffe et al 2017). In addition, diagnosed complications, including retinopathy, CVD and neuropathy were significantly more frequent in patients with DN than in patients without DN.…”
Section: Discussionsupporting
confidence: 80%
“…In this context, logistic regression model revealed that the predicted factors of DN were duration of diabetes, smoking, retinopathy, CVD, neuropathy, glucose, urea, creatinine, cholesterol, LDL-C and GFR. Most of these factors were identified as clinical and biochemical predictive factors in diabetic kidney disease progression (Grover et al 2012;Radcliffe et al 2017). However, the exact stage of DN is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of cholesterol control in T2DM was also important throughout the study ( Table ). Although not many studies have reported HDL as a risk factor to develop DN, these findings seem to be in agreement with previous reports suggesting dyslipidemia as a potential risk marker for diabetic kidney disease . Other investigations have reported a cross‐sectional relationship between the lipid‐subtype “fingerprint” and advanced kidney disease .…”
Section: Discussionsupporting
confidence: 91%
“…The inclusion of time varying attributes in the analysis may be advantageous to predict the outcome. Interestingly, the slopes of change after years 1, 2, and 3 of the study (s1., s2., and s3.Trig in Table ) became important predictors beginning at year 2, suggesting that the lipid control over time is extremely important in patients with T2DM, especially in those with cardiovascular risks who have shown a correlation with dyslipidemia under such conditions …”
Section: Discussionmentioning
confidence: 97%
“…An estimated 382 million people around the world had diabetes in 2013, a number that is expected to rise to 592 million by 2035 . Diabetic kidney disease (DKD) is one of the primary micro‐vascular complications of the disease, and is the leading cause of chronic kidney disease (CKD) and end‐stage renal/kidney disease (ESRD/ESKD) . DKD is typically represented by damage to the glomerulus, interstitium and blood vessels; however, its pathogenesis and molecular mechanisms are not fully understood .…”
Section: Introductionmentioning
confidence: 99%